A Risk-Based Approach for Selecting Software Requirements - Amaral, Aruan; Elias, Gledson (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6055, 2017)
In incremental development approaches, there is a great interest in delivering system releases on-time and on-budget, raising the satisfaction level of the stakeholders involved in the development process. Thus, the software requirements selection process has a key role in identifying a good-enough or even an optimal subset of candidate requirements, which can balance trade-offs among critical aspects, such as project budget, requirements costs, customers’ preferences and their importance. Despite relevant contributions, current proposals do not address software risks involved in the development process, which represents another key aspect that can deeply impact on project cost and stakeholders’ satisfaction. In such a direction, this paper proposes a risk-based approach for selecting software requirements, in which a risk analysis is incorporated for estimating the impact of risks in the cost of the next release requirements and stakeholders’ satisfaction. Evaluation results based on a pilot use case reveal the potential practical applicability of the proposed approach.